The aerodynamic derivatives with respect to sideslip for a delta wing with small dihedral at supersonic speeds - Robinson, A.; Hunter-Tod, J. H. (College of Aeronautics, 1947)
Expressions are derived for the sideslip derivatives on the assumptions of the linearised theory of flow for a delta wing with small dihedral flying at supersonic speeds. A discussion is included in the appendix on the relation between two methods that have been evolved for the treatment of aerodynamic force problems of the delta wing lying within its apex Mach cone. Continues…